Efficacy of a peer-delivered group psychological intervention to reduce psychological distress among university students in India: a randomised controlled trial using an active control condition - Dharani Keyan; Katie S. Dawson; Srishti Yadav; Suzanna Azevedo; Jasmine Choi-Christou; Deepthi J. Maliakkal; Mohan K. Pillai; Ritika Chokhani; Elizabeth Thomas; Tony S. George; Richard A. Bryant (European Journal of Psychotraumatology)
Background: Brief psychological interventions in low-and-middle-income-countries (LMICs) have been typically tested against usual or enhanced usual care (EUC). This design precludes understanding of the role of non-specific factors in influencing outcomes.Objective: This study evaluated an adapted version of WHO’s Problem Management Plus (gPM+), titled Coping with COVID, against an active control condition to reduce anxiety and depression during the COVID-19 pandemic.Methods: In this two-arm, single-blind, randomised controlled trial, young adults aged 18–24 years who screened positive for COVID-19 related psychological distress in Bengaluru (India) were randomly allocated to either Coping with COVID (n = 91) or non-directive Supportive Counselling (SC; n = 92) groups. Coping with COVID was a 6-sesion, group-based programme that taught coping strategies for stress. SC was a 6-sesion, group-based programme that offered non-directive support. The primary outcomes were anxiety and depression as measured by the Hospital Anxiety and Depression Scales (HADS) assessed at baseline, post-intervention, 2-months (primary outcome timepoint), and 6-months after treatment. Secondary outcomes included generalised worry, positive wellbeing, pandemic-related stress, and suicidal ideation.Results: Between October 2021 and December 2022, 183 participants were enrolled into the trial. Relative to SC, Coping with COVID did not lead to significant reductions in anxiety (mean difference 0.24 [95% CI, −1.01,1.48], p>.05), or depression (mean difference .03 [95% CI, −1.19, 1.26], p>.05). Similarly, there were no significant differences between conditions for all secondary outcomes.Conclusions: The findings suggest that the benefits of strategies that comprise transdiagnostic scalable psychological interventions may not surpass non-specific factors in driving symptom reduction.Clinical implications: There is a need to further evaluate the role of non-specific factors in scalable psychological programmes because focusing on these may have implications for ease of training and implementation.Trial registration: Australian New Zealand Clinical Trials Registry identifier: ACTRN12621001064897.